Kinetic of Alkaloids Extraction from Plant by Batch Pertraction in Rotating Discs Contactor - M. Abed, Khalid (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
A liquid membrane process of Alkaloids extraction from Datura Innoxia solution was studied applying pertraction process in rotating discs contactor (RDC). Decane as a liquid membrane and dilute sulphuric acid as stripping solution were used. The effect of the fundamental parameters influencing the transport process, e.g. type of solvent used, effect of disks speed, amount of liquid membrane and effect of pH for feed and strip solution. The transport of alkaloids was analysed on the basis of kinetic laws of two consecutive irreversible first order reactions. Thus, the kinetic parameters (k1, k1, , tmax, and ) for the transport of alkaloids were determined. The effect of organic membrane type on percentage of Alkaloids transport was found to be in the order (n-decane> n-heptane> n-hexane> ethyl ether). The results showed that the highest alkaloids extraction was obtained when using two stages, (10 rpm) discs speed, (pH=9.5) of feed solution and (pH=2) of acceptor solution in n-decane. Observation showed that the membrane entrance rate constant k1 and percentage of alkaloids transported in strip phase increased with increasing numbers of stages but the exit rate constant k2 decreased. The alkaloids extraction ratio increased with increasing the disks speed from 5 to 10 rpm but decreased at 15 rpm and decreased when increasing the volume of membrane. Also pH of feed and strip solution affected the extraction ratio and rate constants.